Enhancing higher education quality through strategic human resource planning: evidence from international colleges - Tubagus Achmad Darodjat; Supot Rattanapun (Institute of Advanced Engineering and Science, 2026)
This research attempts to improve the quality of education at International College, Rajamangala University of Technology (IC-RMUT), applying qualitative research methods that describe human resources planning (HRP). Interviews, observations, and document review were used to collect data from 27 purposively selected informants at nine RMUT universities- administrators, lecturers, and support staff members of International Colleges. Data collection was conducted through interviews, observation, and review of documentation. The analysis technique uses a qualitative data analysis model with the broadest stages of data collection, analysis, and conclusions. Results of the research relate to preparing HRP and adhering to the vision and mission of the IC-RMUT. Then reviewing and reformulating periodically according to student developments and factors that can influence HRP in its implementation. The paper examines obstacles faced in implementing HRP such as the large number of changes in leadership and lecturers. It also looks at the inconsistent application of the human resources management (HRM) concept and how it affects one target and another activity and ultimately HRP activities become undirected.